2016
DOI: 10.1175/jcli-d-15-0536.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Variability of the South Pacific Convergence Zone Using Satellite and Reanalysis Wind Products

Abstract: The variability of the South Pacific convergence zone (SPCZ) is evaluated using ocean surface wind products derived from the atmospheric reanalysis ERA-Interim for the period of 1981–2014 and QuickSCAT for the period of 1999–2009. From these products, indices were developed to represent the SPCZ strength, area, and centroid location. Excellent agreement is found between the indices derived from the two wind products during the QuikSCAT period in terms of the spatiotemporal structures of the SPCZ. The longer ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
5
24
0
Order By: Relevance
“…The Southern Hemisphere is characterized by two regions with quasi-persistent convection, the South Pacific Convergence Zone (SPCZ) and the SACZ. The SPCZ extends from the tropical West Pacific southeastward into the Central Pacific subtropics (Trenberth, 1976) and is characterized by variability from intraseasonal to decadal time scales (Kidwell et al, 2016). The convective heating in the SPCZ is a significant Rossby wave source (Meehl et al, 2001;Shimizu & de Albuquerque Cavalcati, 2011), affecting the mean Pacific flow (van der Wiel et al, 2016).…”
Section: Southern Hemispherementioning
confidence: 99%
“…The Southern Hemisphere is characterized by two regions with quasi-persistent convection, the South Pacific Convergence Zone (SPCZ) and the SACZ. The SPCZ extends from the tropical West Pacific southeastward into the Central Pacific subtropics (Trenberth, 1976) and is characterized by variability from intraseasonal to decadal time scales (Kidwell et al, 2016). The convective heating in the SPCZ is a significant Rossby wave source (Meehl et al, 2001;Shimizu & de Albuquerque Cavalcati, 2011), affecting the mean Pacific flow (van der Wiel et al, 2016).…”
Section: Southern Hemispherementioning
confidence: 99%
“…In fact, the variability of SPCZ convection often reflects interactions across multiple time scales; for example, the phase of ENSO or the MJO may modify the behavior of synoptic-scale interactions with SPCZ convection (Matthews 2012). Kidwell et al (2016) examined various metrics for characterizing SPCZ variability (e.g., intensity, areal extent, centroid latitude) and found that these metrics behave differently depending on the time scale of the variability.…”
Section: Introductionmentioning
confidence: 99%
“…Upon reaching the SPCZ region, wave activity converges due to the decrease in zonal wind speed (Widlansky et al 2011, Matthews 2012, van der Wiel et al 2015. While intraseasonal variability of the SPCZ is related to the Madden-Julian Oscillation, its interannual-to-decadal variability depends on El Niño/Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (Kidwell et al 2016). Large decadal variations in the SPCZ position since 1600 have been suggested based on ocean salinity proxies (Linsley et al 2006).…”
Section: Introductionmentioning
confidence: 99%